2021
DOI: 10.11594/baerj.02.01.07
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Character Education Through School Culture in The New Normal Era: A Case Study at Al-Karim Lampung Basic Natural School

Abstract: Strengthening character education in schools is a government policy as an effort to re-put character as the core of education. The process of teaching and learning activities is currently carried out online and face-to-face while still prioritizing health protocols due to the pandemic. So, currently schools are required to continue to innovate in order to maximize the character education process in schools. The purpose of this study is to describe the strengthening of character education through school culture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The results showed that boarding school However, this study has limitations, such as limited time to observe the long-term effects of the murajaah method on students' disciplinary attitudes. (Saputra & Budimansyah, 2021) In the context of pesantren, the murajaah method can be an approach in developing students' disciplinary attitudes. Murajaah can be used as a means for santri to strengthen their awareness of their obligations in performing worship, maintaining discipline, and carrying out the rules in the pesantren.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that boarding school However, this study has limitations, such as limited time to observe the long-term effects of the murajaah method on students' disciplinary attitudes. (Saputra & Budimansyah, 2021) In the context of pesantren, the murajaah method can be an approach in developing students' disciplinary attitudes. Murajaah can be used as a means for santri to strengthen their awareness of their obligations in performing worship, maintaining discipline, and carrying out the rules in the pesantren.…”
Section: Resultsmentioning
confidence: 99%